Natural attenuation in the vadose zone: Nature’s gift to mine closure - Bowell, RJ (Mine Closure 2023: Proceedings of the 16th International Conference on Mine Closure, 2023)
Natural geochemical attenuation in the vadose zone refers to the process by which chemical parameters are naturally degraded, transformed, or immobilized as they migrate through the unsaturated zone above the water table. The vadose zone that often underlies mine waste facilities is a chemical active environment that involves physical, biological, and chemical interactions. These processes can effectively reduce the concentrations and mobility of contaminants, leading to their eventual removal or degradation. Here are some key natural attenuation processes that can occur in the vadose zone: Biodegradation: Microorganisms present in the soil can metabolize certain chemicals such as ammonia, cyanide or nitrates, breaking them down into simpler and less toxic compounds. Sorption and adsorption are processes by which chemical parameters can be chemically or physically trapped or bound to soil particles through the mechanisms of sorption or adsorption. This can reduce their mobility and availability for further transport. These processes are a function of the pH and redox of the environment, minerals present in the soil and prevailing water chemistry. Volatilization can also occur within the vadose zone and is an important control on the removal of parameters such as cyanide and ammonia. In addition, other chemical reactions may occur involving oxidation-reduction reactions, hydrolysis, and photolysis that can lead to precipitation or incorporation of chemical parameters into non-soluble mineral forms. In addition, although not often spoken about dilution by lower concentration waters in the vadose zone, can reduce or mitigate groundwater impacts. The effectiveness of natural attenuation in the vadose zone depends on several factors, including the nature of the chemicals, the redox and pH potential of the environment, soil properties, groundwater flow rates, and site-specific conditions, such as the availability of oxygen, nutrients, and suitable microbial populations. Such processes can occur in a wide variety of environments. Natural attenuation is an important aspect in long-term management of chemical loading in the environment and whilst it has limitations, combined with other methods such processes are effective in mine closure and should be considered in the planning and assessment of long-term geochemistry in post closure facilities.
Keywords: Natural Attenuation